The analysis of distribution of rare elements in coals and ashes the field of Kazakhstan - G.Zh. Mukhanova; V.S. Portnov; S.A. Vyzhva; N.V. Reva; А.D. Мaussymbayevа (Қарағанды университетінің хабаршысы. Физика сериясы)
The increased contents of various metals, in particular rare elements are connected with coals. Coals of Kazakhstan in general are poorly studied on a complex of passing valuable and toxic elements impurity. In this article for detection of features of concentration and definition the maintenance of rare elements, and also regularities of their distribution in coals, are used the references containing results of analyses on the average content of elements on coal fields of the Republic of Kazakhstan. Consistent patterns of change of average contents rare (scattered, rare-earth) elements from age, an ash-content and degree of a metamorphism of coals are determined. Influences the maintenance of toxic elements in ashes, dust are considered. Communication of rare elements with an ash-content of coals of the Ekibastuz basin are presented by graphs change of averages the maintenance of Ce, La, Tb, Yb, Sm and U in ashes and coal. The average maintenance of radioactive elements as Th and U is also studied. Studying of rare elements in coals began to be carried out relatively recently therefore, possibilities of comparison of the studied coals with coals of other pools are limited.